2019
DOI: 10.1017/s1047951119002671
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of children with congenital heart disease needing diaphragm plication

Abstract: Background:Diaphragm dysfunction following surgery for congenital heart disease is a known complication leading to delays in recovery and increased post-operative morbidity and mortality. We aimed to determine the incidence of and risk factors associated with diaphragm plication in children undergoing cardiac surgery and evaluate timing to repair and effects on hospital cost and length of stay.Methods:We conducted a multi-institutional retrospective observational cohort study. Forty-three hospitals from the Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Waiting after confirming diaphragmatic dysfunction results in a prolonged need for ventilatory/respiratory support, recurrent intubation, increased risk of postoperative pneumonia, prolonged ICU and hospital stay, and even mortality. In a multicenter study of 112,110 patients from 43 hospitals through the pediatric health information system database, the authors found a 2.2% overall incidence of diaphragmatic paralysis, with 24% (603 patients) requiring plication [1]. The authors also noted that infants under one month of age exhibited the greatest requirement for plication, and conversely, as the child's age increased, the likelihood of necessitating plication diminished.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Waiting after confirming diaphragmatic dysfunction results in a prolonged need for ventilatory/respiratory support, recurrent intubation, increased risk of postoperative pneumonia, prolonged ICU and hospital stay, and even mortality. In a multicenter study of 112,110 patients from 43 hospitals through the pediatric health information system database, the authors found a 2.2% overall incidence of diaphragmatic paralysis, with 24% (603 patients) requiring plication [1]. The authors also noted that infants under one month of age exhibited the greatest requirement for plication, and conversely, as the child's age increased, the likelihood of necessitating plication diminished.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 147 patients underwent repeat sternotomy between September 2011 and August 2021. Inclusion criteria were children (<18 years of age) who underwent repeat sternotomy for procedures that either (1) required dissection close to the phrenic nerve, or (2) are known to be associated with phrenic nerve injury. These included distal pulmonary arterial reconstruction, unifocalization, change to the pulmonary conduit, bidirectional cavopulmonary anastomosis, Fontan, aortic arch repair, and heart transplantation.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Konjenital kalp cerrahisinde frenik sinir hasarı postoperatif morbiditeyi önemli derece etkileyen bir komplikasyondur 23 . Frenik sinir hasarında olası mekanizmalar direk yaralanma, koter kullanımına bağlı termal hasar, kontrolsüz timus diseksiyonu, askı dikişlerinin konulmasında ve traksiyonunda oluşan hasarlar, internal juguler ven kanülasyonu ve miyokardiyal korunmada uygulanan topikal soğuk olarak özetlenebilir 20 .…”
Section: Materyal Ve Metotunclassified
“…Without a national clinical registry, administrative and claims‐based databases such as the Pediatric Health Information System (PHIS) are frequently used for source data in outcomes research. PHIS data have generated more than 150 studies involving cardiac disease alone (Beach et al, 2019; Diaz et al, 2019; Foster et al, 2020; Purifoy, Spray, Riley, Prodhan, & Bolin, 2019; Savla et al, 2019; Spinner et al, 2020; Weiner et al, 2020). Despite the widespread use of this database, PHIS accounts for only 15% of nationwide pediatric discharges.…”
Section: Introductionmentioning
confidence: 99%